2015
DOI: 10.4265/bio.20.239
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Characteristics of Heated Eggshell Powder

Abstract: Eggshells have high bioavailability and can be used as a source of calcium. The main component is CaCO 3 , which, when heated, is converted to CaO. Seashells are also mainly composed of CaCO 3 and were previously found to exhibit antimicrobial activity after being heated. In this study, heated eggshell powder HESP was found to have antimicrobial activity against bacterial vegetative cells, fungi and bacterial spores. Parameters, such as the minimum inhibitory concentration, were determined with kinetic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Furthermore, the results of bactericidal against E.coli bacteria were lower for PLA and its composites as compared with staph (34, 45, 52 and 61) % for PLA and its composites. This results agreed with [30] that explained antibacterial activity of PLA against grampositive more than gram-negative because of E. coli has proteins, lipopolysaccharides (LPS) and lipidsin the membrane of his cell which supplied effective protection against biocides, while [31] their results in its agreed with our results when explained ability of eggshell to inhibit the growth of gram-positive and negative bacteria and this ability increased when the concentration was increased too. The mechanism action of eggshell belongs to converted CaCO3 to CaO when it's heated and the hydration process of CaO, which produces alkaline solution conditions, is viewed as an essential EDP activity component.…”
Section: Anti-bacterial Resultssupporting
confidence: 91%
“…Furthermore, the results of bactericidal against E.coli bacteria were lower for PLA and its composites as compared with staph (34, 45, 52 and 61) % for PLA and its composites. This results agreed with [30] that explained antibacterial activity of PLA against grampositive more than gram-negative because of E. coli has proteins, lipopolysaccharides (LPS) and lipidsin the membrane of his cell which supplied effective protection against biocides, while [31] their results in its agreed with our results when explained ability of eggshell to inhibit the growth of gram-positive and negative bacteria and this ability increased when the concentration was increased too. The mechanism action of eggshell belongs to converted CaCO3 to CaO when it's heated and the hydration process of CaO, which produces alkaline solution conditions, is viewed as an essential EDP activity component.…”
Section: Anti-bacterial Resultssupporting
confidence: 91%
“…However, there were 0.29/0.21 and 0.45/0.34 cm inhibition zones in E. coli / S. aureus cells of the MPLA/TWWSSP (3 wt %) (9) and MPLA/TWWSSP (5 wt %) (10) composites, respectively. These results likely resulted from the presence of Ca­(OH) 2 , and CaO, , and more specifically from the release of hydroxyl ions and active oxygen species generated at the TWWSSP surface, which inactivated the microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…The antimicrobial activity of NCS ceramics could be due to calcinated eggshells. It is reported that calcium oxide produced in eggshell that is calcined at a temperature of about 900°C can impart antimicrobial activity to the composition . Bacterial adhesion to the implant material is the main cause of implantation infections that lead to the failure of implanted material.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that calcium oxide produced in eggshell that is calcined at a temperature of about 900°C can impart antimicrobial activity to the composition. [52][53][54] Bacterial adhesion to the implant material is the main cause of implantation infections that lead to the failure of implanted material. Several studies have been reported on ion-based modification by doping the antibacterial agent (Ag, Cu, and Zn) for improving antimicrobial activity of calcium silicate ceramics.…”
Section: Antimicrobial Activitymentioning
confidence: 99%